Co-producing a ‘creative toolkit’ to support the mental health and wellbeing of palliative care professionals: a community case study - Clancy, Marie A.; Kight, Caitlin R.; Stein, Jessica; Glanville, Naome; Wilson, Anthony C.; Kyle, Richard G. (Frontiers in Sociology, 2025)
Alterations to the clinical, social, and economic landscape have made palliative care an increasingly challenging sector in which to work; COVID-19 introduced further changes that pushed palliative care professionals to the breaking point. Their struggles at work are exacerbated by the fact that specialists in this field tend to ignore their own needs, instead centring and prioritising those of their patients—a situation that is not tenable. Within this community case study we describe how our team, comprising clinical and university staff, sought to address this by co-creating a suite of resources to support the physical, psychological, social, and spiritual health of palliative care workers. The result was the Creative Toolkit©, which is both an overall approach and a suite of materials that uses creative, arts-based intervention to facilitate reflection, relaxation, and rejuvenation—and to ensure that clinical staff feel connected and valued. Although participants sometimes initially hesitate due to their limited prior exposure to art-based methods, feedback on our sessions has been unanimously positive, revealing the value of creative activities for, among other things, aiding in processing difficult feelings and creating community amongst staff. While initial results are promising, we acknowledge the need for an expanded evidence base to encourage more widespread uptake of our method.